Comparação do efeito do bochecho de triclosan + copolímero + fluor, com a clorexidina, sobre a taxa de formação da placa dentária, retenção de antimicrobiano na placa dentária e na saliva e redução de estreptococos do grupo mutans na saliva: estudo clínico randomizado, cruzado, duplo-cego controlado - Vaz, Vanessa Torraca Peraro [UNESP] (2014)
The aim of this study was to comparatively evaluate the effect of daily rinsing with a solution of chlorhexidine digluconate 0,12% (TA- control) with the solution 0,03% triclosan + 1% copolymer (Gantrez ® ) + sodium fluoride 0,05% (TB- test) according of the rate of dental plaque formation, retention of antimicrobial agent in dental plaque and saliva by high performance liquid chromatography and reduction on mutans streptococci in saliva .Material and Method: In this randomized clinical study, crossover, double blinding with two treatment periods, 26 volunteers of both genders with between 18-30 years ( average 24 years), was divide into 2 groups: G1 (n=13) and G2 (n=13). In each treatment period the volunteers realized two daily mouthwashes of 60 seconds each, the first to get up and other twelve hours later, for 7 days. Results: The reduction of rate of dental plaque formation was same in bouth groups; high performance liquid chromatography analysis wasn’t show trace of antimicrobial after 12 hours use of mouthwashes by 1 or 7 days in dental plaque or in saliva .The antimicrobial action showed statistically significant effect for treatment (before and after rinsing) with antimicrobial agent (chlorhexidine x triclosan). The chlorexidine digluconate was more effective than triclosan (22,8% and 8,9 decrease, respectively). Conclusion: 1) As far as triclosan, chlorhexidine, were effective in reducing dental plaque volunteers. 2) None of the antimicrobial agents remain in the oral cavity after 12 hours of use. 3) The use of mouthwashes containing chlorhexidine and triclosan, complements the mechanical control of dental plaque for their effective antimicrobial action on mutans streptococci, reducing caries risk patients.